The seasonal succession of diatoms in phytoplankton of a soda lake (Lake Hazar, Turkey) - Kocer, Mehmet Ali Turan; Sen, Bulent (Tubitak Scientific & Technological Research Council Turkey, 2012)
Some physicochemical variables and climatic effects on the succession of a diatom community in the plankton of the pelagic zone of Lake Hazar, an alkaline soda lake, were investigated. Monthly diatom samples were collected from the surface water at western, central, and eastern pelagic areas of the ellipsoid-shaped lake using a plankton net from November 2004 to October 2005. When high temperature and pH levels prevailed in May and September, Epithemia, Rhopalodia, Cocconeis, and Cyclotella were dominant. Cymbella was dominant in early spring and late autumn, but was not significantly correlated with temperature or pH. The species of Gomphonema, Fragilaria, Navicula, and Nitzschia were dominant at low temperature and pH levels in winter. However, the diatom community of the surface phytoplankton in the lake comprised largely cosmopolitan and nonplanktonic species of Cocconeis, Cyclotella, Cymbella, Epithemia, Fragilaria, Gomphonema, and Rhopalodia detached from benthic habitats of littoral zone by wind-driven currents.
Keywords: Diatom; succession; water quality; soda lake